Associations de la variabilité de la fréquence cardiaque au second seuil ventilatoire avec la vitesse de course maximale et les performances de course sur 5 et 10 km - Junior, A. F.; Giovanini, B.; Altimari, L. R. (Science & Sports, 2024)
Lactate threshold (LT) and second ventilatory threshold (VT2) are variables determined during the incremental running test. LT and VT2 are associated with endurance performance and can be used for training prescriptions. However, LT and VT2 measurements require expensive equipment and qualified personnel - which makes their practical application difficult for coaches and athletes. To this concern, the analysis of heart rate variability threshold (HRVT) using a portable cardiac monitor during a maximal incremental test is an alternative and affordable method to estimate the LT and the VT2. Previous studies indicate that the second HRVT (HRVT2) is strongly associated with LT, and VT2, which could be an alternative low-cost measurement to use during training prescriptions.